2009
DOI: 10.1108/02686900910966503
|View full text |Cite
|
Sign up to set email alerts
|

Strategy, control activities, monitoring and effectiveness

Abstract: Purpose -First, this paper aims to provide empirical evidence of the interaction between the components of an internal control system. Second, it seeks to integrate work from the field of strategy and that on the internal control system from the field of auditing. The purpose of this paper is to enable a more profound understanding of how different strategic orientations may influence effectiveness, depending on the components of the internal control system. Design/methodology/approach -Data were collected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 38 publications
3
38
0
1
Order By: Relevance
“…Internal control is a multidimensional concept and has been discussed in many ways in the management control literature (Agbejule & Jokipii, 2009;Bowrin, 2004). It is not solely a procedure or policy that is performed at a certain point in time.…”
Section: Internal Control System For Accountability In Public Sectormentioning
confidence: 99%
“…Internal control is a multidimensional concept and has been discussed in many ways in the management control literature (Agbejule & Jokipii, 2009;Bowrin, 2004). It is not solely a procedure or policy that is performed at a certain point in time.…”
Section: Internal Control System For Accountability In Public Sectormentioning
confidence: 99%
“…This issue is addressed very often and at several levels within the country , in spite of the fact that Jordanian human resources are of the best skills in the region and of Jordan's remarkable reputation in several fields for example the ICT and regulatory sectors (Kateb et al, 2014;Altamony et al, 2016). The internal control system consists of all the variables that may contribute some way or another to the success or failure of any organization and by establishing a robust internal control system the organization promotes efficient and effective operations to produce quality products and services that are consistent with its objectives and goals (Agbejule & Jokipii, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the type of internal control activities which are implemented in business entities, these activities need not only to function appropriately, but should also be adaptable to changes in applicable environments (e.g. economic environments, political environments and technological environments) to optimally mitigate risks (Agbejule & Jokipii, 2009). By doing so, these activities will reasonably assure management that the relevant business entity will attain its objectives in the foreseeable future which, in turn, relate to the fulfilment of associated economic responsibilities, social responsibilities and/or environmental responsibilities (Rodgers, 2010) (Buys, 2012) (Bechtold, et al, 2013).In most cases, the manner in which economic responsibilities are fulfilled will ultimately determine whether a business entity will fail or not (Amendola, Giordano, Parrella, & Restaino, 2017) (Small, Smidt, & Joseph, 2017).Notwithstanding the above, in a South African SMME dispensation, two local studies (Siwangaza, 2013) (Bruwer, 2016) (Bruwer, Coetzee, & Meiring, 2017) found that internal control activities are regarded as ineffective and/or inadequate as they do not provide reasonable assurance surrounding the attainment of relevant pre-determined business objectives in the foreseeable future.…”
Section: Internal Control Activitiesmentioning
confidence: 99%